Family waqf in Islamic law: an analysis of its socio-legal significance - Sadique, Muhammad Abdurrahman (2015)
It is established that the creation of awqaf for the primary benefit of one’s relatives and descendants was an original innovation of Islam. It has been argued that family waqf endowment is a superior avenue of charity, as such awqaf endeavour to prevent the descendants of the endower from becoming needy of others, thus eliminating poverty and need at root. Some governments in Muslim countries had chosen to impose various degrees of restrictions on the creation or functioning of family awqaf, based on the conventional approach that charity should necessarily be directed towards the public, rather than one’s kith and kin. Mismanagement of such awqaf and their failing to fulfil their objectives, has been cited as the key arguments favouring such restrictions. Weaknesses in the judicial system as well as state governance had led to the deterioration in awqaf in addition to mismanagement. Individual management has been proposed as the best suited method for awqaf, while management of investment oriented awqaf should be handled by institutions apart from state, that preserve its nature as a third sector, dissociated from the private sector.